Volatile profiling as a potential biochemical marker for validation of gamma irradiation derived putative mutants in polyembryonic genotypes of mango (Mangifera indica L.) - Perveen, Nusrat; Dinesh, M. R.; Sankaran, M.; Shivashankara, K. S.; Ravishankar, K. V.; Venugopal, R.; Mir, Hidayatullah (Frontiers in Plant Science, 2023)
Putative mutants were generated through gamma irradiation in the polyembryonic mango variety Nekkare. The putative mutant progenies along with control seedlings and mother plants were evaluated by comparing the compositions and relative proportions of their major volatile compounds. Volatile profiling was done using headspace-solid phase microextraction (HS-SPME) method coupled with gas chromatography-mass spectrometer (GC-MS-MS). Further, characterization of putative mutants and control seedlings was carried out using Simple Sequence Repeat (SSR) markers to ascertain the genetic diversity present in the samples under study. Monoterpenes were the most abundant volatile compound in all the studied samples (ranging from 34.76-91.41%) out of which I-Phellandrene and cis-Ocimene formed the major fraction in mother plants (20.45-21.86% and 16.17-21.27% respectively) and control seedlings (23.32-24.95% and 18.95-20.81% respectively) while beta-Phellandrene was dominant in the selected putative mutant samples (2.34-29.53%). Among sesquiterpenes, trans-Caryophyllene was detected only in the putative mutant samples (0.10-30.18%). Grouping together of mother plants and control seedlings was seen in the cluster analysis, while the putative mutants grouped apart from them suggesting genetic diversity.Genetic distance between the mother plants and control seedlings ranged from 0.97 to 2.73 while between putative mutants, control seedlings and mother plants it ranged from 6.54 to 9.82. SSR based characterization of putative mutant seedlings showed that mutation caused variability in the treated population. This was evident from the high allelic richness ranging from 4-12 with a mean of 7 and higher mean Shannon's Information index (1.50) of the 2 putative mutant population. The study demonstrates that volatile profiling and molecular characterization using SSR markers could be used as a tool to detect variation in a mutated population. Also, volatile profiling can be used to validate putative mutants in polyembryonic mango genotypes where the seedlings of nucellar origin are similar to mother plants.